Artificial stone-associated silicosis: a rapidly emerging occupational lung disease. Issue 1 (7th September 2017) - Hoy, Ryan F; Baird, Timothy; Hammerschlag, Gary; Hart, David; Johnson, Anthony R; King, Paul; Putt, Michael; Yates, Deborah H
Abstract : Introduction: Artificial stone is an increasingly popular material used to fabricate kitchen and bathroom benchtops. Cutting and grinding artificial stone is associated with generation of very high levels of respirable crystalline silica, and the frequency of cases of severe silicosis associated with this exposure is rapidly increasing. Aim: To report the characteristics of a clinical series of Australian workers with artificial stone-associated silicosis. Methods: Respiratory physicians voluntarily reported cases of artificial stone-associated silicosis identified in their clinical practices. Physicians provided information including occupational histories, respiratory function tests, chest radiology and histopathology reports, when available. Results: Seven male patients were identified with a median age of 44 years (range 26–61). All were employed in small kitchen and bathroom benchtop fabrication businesses with an average of eight employees (range 2–20). All workplaces primarily used artificial stone, and dust control measures were poor. All patients were involved in dry cutting artificial stone. The median duration of exposure prior to symptoms was 7 years (range 4–10). Six patients demonstrated radiological features of progressive massive fibrosis. These individuals followed up over a median follow-up period of 16 months (IQR 21 months) demonstrated rapid decline in prebronchodilator forced expiratory volume in 1 s of 386 mL/year (SD 204 mL) and forced vital capacity of 448 mL/year (SD 312 mL). Conclusions: This series of silicosis in Australian workers further demonstrates the risk-associated high-silica content artificial stone. Effective dust control and health surveillance measures need to be stringently implemented and enforced in this industry.